Comparative Anatomy of Rare Amphibians (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2023)
The Caudata (salamanders) and Gymnophiona (caecilians) represent the two most morphologically and ecologically diverse amphibian orders beyond Anura (frogs), yet their comparative anatomy remains poorly characterised relative to their anuran counterparts, partly because many species are rare, cryptic, fossorial, or restricted to remote tropical habitats that complicate specimen collection. This study applied high-resolution micro-computed tomography (micro-CT; voxel resolution 15–50 µm) and geometric morphometrics to quantify skeletal anatomy in 28 rare and poorly-known amphibian species from six families — Proteidae, Sirenidae, Plethodontidae, Salamandridae, Ichthyophiidae, andDermophiidae — using 284 museum specimens from 14 European and North American natural history collections. Volumetric segmentation of skeletal elements from micro-CT data enabled three-dimensional morphometric comparison of skull, vertebral column, and limb girdle morphology across species representing diverse ecological specialisations (aquatic neotenic, fossorial, scansorial, and semi-aquatic). Phylogenetic signal (Blomberg’s K) was significant for skull length (K = 0.84 ± 0.12; p < 0.001), vertebral count (K = 0.92 ± 0.10; p < 0.001), and limb reduction index (K = 0.78 ± 0.14; p < 0.001), confirming that most skeletal variation reflects phylogenetic history rather than ecological convergence.However, four ecological trait complexes showed significant convergent morphology across distantly related taxa: fossorial caecilian-like skull morphology in unrelated fossorial plethodontids; vertebral elongation in neotenic paedomorphic species; forelimb reduction in caecilians and sirenids; and cranial kinesis reduction in Proteidae. New morphological characters derived from micro-CT data provide 14 synapomorphies with potential phylogenetic diagnostic value not visible in external morphology. These results demonstrate the power of micro-CT-based comparative anatomy for resolving systematic and evolutionary questions in cryptic rare amphibian taxa and provide a three-dimensionalreference atlas for rare amphibian skeletal morphology.